Analisis Implementasi Akad Pembiayaan Murabahah dan Sistem Pengawasan Internal terhadap Keputusan Pemberian Pembiayaan Murabahah : Studi Kasus: Bank BJB Syari’ah KCP Lippo Cikarang - Ang Riqko Suhendi; Iwan Setiawan (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to analyze the implementation of murabahah financing agreements and the role of internal control systems on the decision-making process for providing murabahah financing at Bank BJB Syariah KCP Lippo Cikarang. The study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation to relevant informants in the bank environment. The results of the study indicate that the implementation of murabahah agreements is carried out by considering sharia principles and internal bank provisions, while the internal control system plays an important role in ensuring compliance with regulations, preventing financing risks, and supporting healthy and sustainable financing decisions. These findings provide an illustration that the integration between the implementation of correct murabahah agreements and an effective internal control system can improve the quality of the financing process and reduce the risks faced by banks.